A conditioning acrylic acid suspension thickener, preparation method, composition containing the same, preparation method and application

Through two-step polymerization method and emulsifier compounding technology, an acrylic suspension thickener with high yield value, high viscosity and good conditioning was prepared, which solved the problem of insufficient conditioning and compatibility in the prior art, and achieved the following: Excellent performance in shampoo.

CN116102693BActive Publication Date: 2025-02-18WANHUA CHEM GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202111323727.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-09
Publication Date
2025-02-18
Estimated Expiration
2041-11-09

AI Technical Summary

Technical Problem

In the prior art, when used in shampoo, acrylic thickeners will reduce conditioning and compatibility, and have insufficient ion resistance, which limits their application in the daily chemical industry.

Method used

The conditioning acrylic suspension thickening agent is prepared by a two-step polymerization method. By combining non-ionic and anionic emulsifiers in a suitable proportion, the double bond-containing silicone is introduced to ensure uniform distribution of the silicone oil chain segments, and the product's ion resistance is improved. Conditioning.

Benefits of technology

It achieves high yield value, high viscosity and good conditioning in shampoo, and has low odor and low irritation, improving the ion resistance and formula compatibility of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0003416627290000071
    Figure GDA0003416627290000071
  • Figure GDA0003416627290000081
    Figure GDA0003416627290000081
  • Figure GDA0003416627290000101
    Figure GDA0003416627290000101
Patent Text Reader

Abstract

The present invention discloses a conditioning acrylic acid suspension thickener, a preparation method, a composition containing the same, a preparation method and an application thereof, wherein the composition comprises: (a) 0.01 to 15% of a conditioning acrylic acid suspension thickener; (b) 10 to 30% of a detersive surfactant; (c) 0.01 to 5% of a conditioning agent; and (d) the balance is an aqueous carrier, all based on the total weight of the composition. The composition of the present invention has the characteristics of good conditioning, good ion resistance, stable performance, etc., and is suitable for use as a shampoo.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of cleaning and washing, and in particular relates to a composition containing an ion-resistant suspended polymer, a preparation method and application thereof. Background Art

[0002] With the continuous improvement of living standards, people have continuously put forward new demands for personal cleaning products. For example, to meet a more gorgeous appearance, it is necessary to add pearl powder, petals, soft beads, walnut particles, etc. Usually, acrylic (ester) emulsion thickeners are added to provide sufficient suspension performance on the basis of thickening.

[0003] There are many studies on acrylic acid (ester) emulsion thickeners at home and abroad. Some of them adopt the traditional emulsion polymerization method, and there are also some studies on seed emulsion polymerization. CN201910043683.1 uses reactive nonionic surfactants, methacrylic acid, and acrylic acid ester as reactants, persulfate as polymerization initiator, and sodium dodecyl sulfate as emulsifier, and synthesizes polyacrylic acid anionic thickener by emulsion copolymerization. CN201210160977.0 uses dioctyl polyoxyethylene ether methacrylate as hydrophobic modified functional monomer to prepare acrylic emulsion thickener. After the above-mentioned acrylic polymer is neutralized by adding alkaline substances, the carboxylic acid groups on the main chain of the polymer are ionized to form negatively charged -COO-, and the -COO- on the polymer chain produces mutual Coulomb repulsion, so that the polymer chain begins to stretch, thereby achieving thickening. However, since damaged hair is mainly charged, shampoo in the prior art mainly improves conditioning by adding cationic conditioners. Adding acrylic thickeners to shampoo will greatly reduce conditioning and formulation compatibility.

[0004] The main application fields of the associative (meth) acrylate emulsion thickener synthesized by the existing emulsion polymerization method are water-based coatings, paper pulp, textile printing and dyeing, water-based adhesives, etc. In addition to the thickening effect of the thickener, these fields have no requirements on the odor of the synthetic emulsion, the amount of residual monomers, the transparency of the thickener after neutralization, the composite transparency and viscosity of the ionic surfactant, and the suspension of bubbles and colored particles. Then these performance deficiencies will limit the application of the product in the daily chemical industry, especially the continuous upgrading of consumer demand, which cannot tolerate these performance defects.

[0005] Some existing thickeners that can be used in the daily chemical industry have some problems in terms of transparency of aqueous solution, transparency of compounding, ion resistance, suspension performance and stability of emulsion. For example, patent CN103772625B discloses a product that eliminates high yield value by compounding emulsifiers and neutralizing monomers, but the monomer structure of the product itself is not designed. When it is used in shampoo formula, anionic acrylic emulsion and cationic conditioning agent produce electrostatic complexation, which reduces the amount of deposition during the use of shampoo, and consumers experience that the conditioning is insufficient; and although some associative monomers are introduced into the product, the carbon chain number is too short, and the carbon chain itself is not hydrophobic enough, resulting in insufficient ion resistance in the water phase system, further limiting its application in downstream formulations.

[0006] Therefore, there is still a need for a conditioning acrylic suspension thickener suitable for daily chemical products such as shampoo and a composition containing an ion-resistant suspension polymer. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a conditioning acrylic suspension thickener and a high yield value and high viscosity composition product containing the same, which has good conditioning properties and good ion resistance, and the product has the characteristics of low odor and low irritation.

[0008] Another object of the present invention is to provide a method for preparing the conditioning acrylic suspension thickener and a composition containing the same.

[0009] Another object of the present invention is to provide the application of the composition.

[0010] In order to achieve the above invention object, the present invention adopts the following technical solution:

[0011] A conditioning acrylic suspension thickener is prepared from raw material components with a mass percentage of 20%-35% and 65%-80% deionized water, wherein the raw material components include the following components in mass percentage: 10.0-75.5% of hydrophilic monomer, 15.0-85.0% of hydrophobic monomer, 0-3.0% of cross-linking monomer, 0.5-25.0% of siloxane containing double bonds, 0.1-5.0% of emulsifier, and 0.1-1.0% of initiator.

[0012] In a specific embodiment, the double bond-containing siloxane in the raw material component is selected from at least one of vinyl hydrogen siloxane or divinyl hydrogen siloxane, and the corresponding silicone oil viscosity is 5-20CS;

[0013] Preferably, the hydrophilic monomer is selected from at least one of maleic anhydride, itaconic acid, itaconic acid salt, acrylic acid, acrylate, methacrylic acid, methacrylate, citraconic acid, citraconic acid salt, fumaric acid, fumarate, crotonic acid, crotonate, aconitic acid or aconitate;

[0014] Preferably, the hydrophobic monomer is selected from at least one of styrene, monobutyl itaconate, vinyl acetate, methyl acrylate, ethyl acrylate, butyl acrylate, isopropyl acrylate, isooctyl acrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isopropyl methacrylate, isooctyl methacrylate or hydroxyethyl methacrylate;

[0015] Preferably, the crosslinking monomer is selected from olefins containing two unsaturated double bonds, more preferably at least one of N,N'-methylenebisacrylamide, ethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, triethylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate or diallyl phthalate;

[0016] Preferably, the emulsifier is prepared by compounding a nonionic emulsifier and an anionic emulsifier, wherein the anionic emulsifier is selected from at least one of sodium succinic acid sulfonate, sodium diisobutylnaphthalene sulfonate, sodium dodecylbenzene sulfonate or sodium dodecyl sulfate; the nonionic emulsifier is selected from at least one of Span-80, Tween, alkylphenol polyoxyethylene ether or isomeric alcohol polyoxyethylene ether;

[0017] Preferably, the initiator is a water-soluble persulfate initiator, more preferably at least one of ammonium persulfate, sodium persulfate or potassium persulfate.

[0018] On the other hand, the preparation method of the aforementioned conditioning acrylic suspension thickener comprises the following steps:

[0019] 1) dissolving 17-90% of the total weight of anionic emulsifier in 150-200 parts by weight of water, then adding hydrophobic monomer, hydrophilic monomer and crosslinking monomer, and stirring in an emulsifying kettle to form a pre-emulsion S1;

[0020] 2) dissolving a nonionic emulsifier and an anionic emulsifier in 10 to 40 parts by weight of water at a ratio of 1:4 to 1:5, wherein the anionic emulsifier accounts for 5 to 50% of the total weight of the anions, and then adding a siloxane containing a double bond and a hydrophilic monomer acid, wherein the weight ratio of the siloxane containing a double bond to the hydrophilic monomer acid is 1:5 to 1:1, and stirring in an emulsifying kettle to form a pre-emulsion S2;

[0021] 3) dissolving nonionic and anionic emulsifiers in 130-200 parts by weight of water in a ratio of 1:1 to 1:4, wherein the anionic emulsifier accounts for 5-33% of the total weight of the anionic emulsifier, and adding the mixture to a reaction kettle; dropping the pre-emulsion S1 obtained in step 1) into the reaction kettle, adding 50-90% of the total weight of the initiator to initiate polymerization at a reaction temperature of 80-90° C., and keeping the mixture warm for 1-1.5 hours after the dropping is completed;

[0022] 4) adding the pre-emulsion S2 obtained in step 2) dropwise into the reaction kettle, adding 10-50% of the total weight of the initiator to initiate polymerization at a reaction temperature of 80-90° C., and keeping the temperature for 0.5-3 hours after the addition is completed;

[0023] Wherein, the total weight ratio of the nonionic emulsifier to the anionic emulsifier is 1:10 to 1:4.

[0024] In another aspect, a composition containing an ion-resistant suspension polymer comprises the following components based on the total weight of the composition:

[0025] (a) 0.01 to 15% of the aforementioned conditioning acrylic suspension thickener, preferably 0.5 to 8%;

[0026] (b) 10 to 30% of a detersive surfactant, preferably 15 to 25%;

[0027] (c) 0.01 to 5% of a conditioning agent, preferably 0.1 to 2%;

[0028] (d) The balance is aqueous carrier.

[0029] In a specific embodiment, the component (b) heavy detersive surfactant is selected from at least any one of sodium laureth sulfate, alkyl amino oxides, alkyl betaines, cocamidopropyl betaine, disodium cocoamphodiacetate, alkyl sulfobetaines, alkyl glycinates, alkyl carboxyglycinates, alkylaminopropyl hydroxy, acyl taurates and acyl glutamates, sodium lauryl sulfate, sodium lauryl polyether sulfate, C12-16 alkyl glucoside or sodium lauroyl glutamate, preferably, the alkyl and acyl groups have 8-19 carbon atoms.

[0030] In a specific embodiment, the conditioning agent in component (c) is selected from at least any one of polyquaternium salts, quaternized proteins, cationic guar gums or water-soluble silicone oils; preferably, the conditioning agent is selected from at least any one of guar hydroxypropyltrimonium chloride, polyquaternium-10 or polydimethylsiloxane.

[0031] In a specific embodiment, the aqueous carrier in the component (d) is selected from water and a mixture of one or more of sodium chloride, a pH regulator, an antidandruff agent, a flavor, an emulsifier, a chelating agent, a sunscreen, a preservative, and a pearlescent agent; preferably, the aqueous carrier comprises the following components in percentage by weight, based on the total weight of the aqueous carrier:

[0032] 0-1% pH adjuster;

[0033] 0-3% anti-dandruff agent;

[0034] 0-3% flavor;

[0035] 0-3% emulsifier;

[0036] 0-0.5% chelating agent;

[0037] 0-1% sunscreen;

[0038] 0-1% preservatives;

[0039] 0-1% pearlescent agent;

[0040] 0-1% petal or particle suspension;

[0041] The rest is water.

[0042] The anti-dandruff agent is selected from at least any one of climbazole, pyrithione zinc, piroctone olamine or triclosan, preferably piroctone olamine.

[0043] The preservative is selected from at least one of kasone, paraben, sodium benzoate, salicylic acid, DMDM ​​hydantoin or phenoxyethanol, and sodium benzoate is preferred.

[0044] The fragrance is selected from artificial synthesis or natural fragrances, preferably natural fragrances.

[0045] On the other hand, the preparation method of the aforementioned composition comprises the step of stirring and mixing the components (a) to (d) according to the proportions until they are uniform, wherein heating, cooling, vacuum and the like may be used without any limitation.

[0046] In yet another aspect, the aforementioned composition is used as a shampoo.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] Since the present invention adopts two-step polymerization, the monomers that are easy to generate odor are polymerized in the first step, and heat preservation measures are taken in the middle. After the second step polymerization reaction, the finished emulsion can reduce the residual ethyl acrylate monomer, thereby reducing the product odor.

[0049] The present invention makes the silicone oil chain segments evenly distributed on the polymer segments by polymerization. Compared with adding ordinary silicone oil components after polymerization, the process is simple and the stability of the emulsion is increased. Since the present invention is used in the system to play a thickening role after neutralization, the proportion of hydrophilic acid monomers must be greater than 10%; at the same time, in order to ensure the compatibility of the product and to ensure sufficient transparency in systems such as aqueous solutions, the ratio of acid monomers to hydrophobic silicone oil in the second step reaction is 1:1-1:5.

[0050] In the process of emulsion polymerization, the present invention mainly polymerizes on the periphery of the polymer chain because silicone oil is added in the second step reaction, thus ensuring that the polymer can fully stretch when alkali is added to the formula to dissolve and expand, further enhancing the formula compatibility of the polymer, the hydrophobicity of the silicone oil monomer is relatively high, and the compression effect of a large number of ions on the acrylate double electric layer in the formula can be reduced, so the formula can have stronger ion resistance; at the same time, the introduction of silicone oil components improves the conditioning of the product during use, and the suspension of hydrophobic products such as silicone oil added to the formula is better. Further, in order to ensure the polymerization effect of vinyl silicone oil, the present invention uses vinyl hydrogenated silicone oil with relatively small molecular steric hindrance, which has higher reaction efficiency than vinyl polydimethylsilicone oil, and the final product has better stability, conditioning and compatibility.

[0051] Compared with the traditional emulsion polymerization method of directly dropping monomers, the present invention obtains a stable pre-emulsion containing vinyl silicone oil by compounding nonionic and anionic emulsifiers in appropriate proportions. In addition, the overall emulsifier ratio is also designed, which can not only make the polymerization process more stable, but also reduce the amount of emulsifier used, avoid excessive bubbles in the production process, and improve production efficiency. DETAILED DESCRIPTION

[0052] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.

[0053] The main raw materials and sources of the embodiments are shown in Table 1:

[0054] Table 1. Main raw materials and sources

[0055]

[0056]

[0057] Unless otherwise specified, other raw materials can be obtained through commercial sources.

[0058] The suspension thickening performance of acrylic emulsion in shampoo is mainly characterized by the viscosity and yield value of shampoo. The test methods are:

[0059] ①Use Brookfield viscometer and 64# rotor to measure the viscosity at 0.5r, 1r, and 20r respectively;

[0060] ② The yield value is represented by subtracting the viscosity value measured at 1r from the viscosity value measured at 0.5r and then dividing by 100. The larger the yield value, the better the suspension.

[0061] [Example 1]

[0062] (1) 3.6 g SDS, 200 g water, 110 g EA, 10 g MMA, 40 g BA, 1 g DAP, 1 g MBA, 80 g MAA and 5 g AA were sequentially added into a container for pre-emulsification to obtain pre-emulsion 1.

[0063] 1.8 g SDS, 0.36 g AEO9, 30 g water, 30 g MAA and 15 g VSO 20 were sequentially added into a container for pre-emulsification to obtain pre-emulsion solution 2.

[0064] (2) 0.6 g SDS, 0.3 g AEO9 and 180 g water were added to the reaction kettle, stirring and heating were started, and when the temperature in the kettle rose to 85° C., the pre-emulsion 1 and 225 g 1 wt % APS aqueous solution were added dropwise for a total of 1.5 h. After the addition was completed, the mixture was kept warm for 1 h. Then, the pre-emulsion 2 and 75 g 1 wt % APS aqueous solution were continued to be added dropwise for a total of 1 h. After the addition was completed, the mixture was kept warm for 1 h.

[0065] (3) Cooling to 30° C., adding water to adjust the final solid content to 30%, filtering the material to obtain the final acrylic emulsion.

[0066] [Example 2-6]

[0067] According to the method in Example 1 and using the raw material amounts in Table 2, the acrylic emulsions of Examples 2-3 were prepared.

[0068] [Comparative Examples 1-9 and Comparative Examples 11-12]

[0069] Referring to the method in Example 1, the acrylic emulsions of Comparative Examples 1-9 and Comparative Examples 11-12 were prepared using the raw material amounts in Table 2.

[0070] [Comparative Example 10]

[0071] (1) According to the amount of pre-emulsion in the table, pre-emulsion 1 and pre-emulsion 2 are obtained.

[0072] (2) 0.6 g SDS, 0.3 g AEO9 and 180 g water were added to the reactor, stirring and heating were started, and the temperature in the reactor was raised to 85°C. Pre-emulsion 1, emulsion 2 and 300 g 1 wt% APS aqueous solution were added dropwise at the same time. The addition was continued for 2.5 hours. After the addition was completed, the mixture was kept warm for 2 hours.

[0073] (3) Cooling to 30° C., adding water to adjust the final solid content to 30%, filtering the material to obtain the final acrylic emulsion.

[0074] Table 2, the amount of each raw material in the examples and comparative examples / g

[0075]

[0076] A Emulsion Performance

[0077] Stability test: Place the emulsion in a 50-degree oven for one month, take it out and observe whether there is stratification or oil floating. Filter it and observe the change of residue content. If the residue content exceeds 500, it is unqualified.

[0078] Odor evaluation: Ten odor evaluation panel members were recruited to rate the odor of the lotion (1-5 points), with 1 being the worst odor and 5 being the best odor.

[0079] After the stability and odor meet the requirements, the water phase performance and formula performance are evaluated.

[0080] B Water Phase Performance Evaluation

[0081] Preparation of aqueous phase sample: 3.3 g of acrylic emulsion was added to 96.7 g of water, and then neutralized with 18% NaOH aqueous solution to pH = 6.5, and the transparency and viscosity at this time were tested.

[0082] Transparency test: After the transparency instrument self-check is completed, preheat for 20 minutes. Determine the wavelength of 420nm, perform zero calibration based on pure water, put in the sample, and read the transparency value.

[0083] Viscosity test: After the system self-check is completed, place the container containing the sample to be tested on the container seat, select 20rpm, immerse the rotor in the sample to be tested, and make the mark on the stirring blade shaft flush with the liquid surface. The instrument automatically starts to run, and the viscosity value is read after the data stabilizes after a few seconds.

[0084] Ion resistance test: After adding 0.3g NaCl to the above sample, repeat the viscosity test and calculate the ratio to the viscosity value before adding NaCl.

[0085] C formula performance test

[0086] The shampoo formula is prepared by using the acrylic emulsion obtained in the above examples and comparative examples. The formula is shown in Table 3:

[0087] Table 3. Shampoo formula

[0088]

[0089]

[0090] Note: Raw materials without manufacturer identification can be used as long as they are of the same type.

[0091] The specific preparation method is:

[0092] Add the prepared acrylic emulsion to deionized water, start stirring, add sodium laureth sulfate at 300 r / min, then neutralize with 18% NaOH aqueous solution to pH = 6.5, and gradually increase the speed to 800 r / min, stir for 10 minutes, add cocamidopropyl betaine, polyquaternium-10, PHCG and essence at once, and continue stirring for 30 minutes to obtain shampoo.

[0093] The shampoos prepared from the acrylic emulsions of the embodiments and comparative examples were tested for their suspension and thickening properties.

[0094] Shampoo viscosity test: After the system self-check is completed, place the container containing the sample to be tested on the container seat, select 0.5rpm, 1rpm, 20rpm respectively, immerse the rotor in the sample to be tested, and make the mark on the stirring blade shaft flush with the liquid surface. The instrument automatically starts running, and after a few seconds when the data stabilizes, record the viscosity value at 20rpm.

[0095] Shampoo yield value test: According to the previous viscosity values ​​of 0.5rpm and 1rpm, calculate the yield value = (η 0.5r -η 1r ) / 100

[0096] Further performance testing on the hairbrush:

[0097] Hair bundle smoothness test: 15 wt% sodium laureth sulfate solution was used to wash two groups of unused hair bundles, and the combing work was obtained as the initial combing work using the above-mentioned MTT175 hair tester, and recorded as W initial1 , W initial2 ; The hair bundle is washed with a twenty-fold diluted test shampoo (containing a polymer) and a blank shampoo (without any conditioner), and the test combing work and the blank combing work are obtained by the above test steps and recorded as W respectively. test and W blank The combing smoothness index can be recorded as:

[0098] Smoothness index = (W blank / W initial2 -W test / W initial1 )*100%.

[0099] The shampoos prepared from the acrylic emulsions of the embodiments and comparative examples were tested for suspension thickening performance, and the performance evaluation results are shown in Table 4:

[0100] Table 4. Comparison of viscosity and suspension properties of shampoo formulas

[0101]

[0102]

[0103] It can be seen from Examples 1-10 that with appropriate emulsifier ratios and monomer combinations, a stable emulsion can be obtained, and has good viscosity, transparency and ion resistance in water, a high yield value in the formula (generally, the yield value of products that are difficult to suspend should be >180), and good product conditioning properties after use.

[0104] By comparing Examples 1-2 with Comparative Examples 1-2, it can be found that when the ratio of hydrophilic acid to hydrophobic silicone oil introduced into the pre-emulsion S2 added in the second step is too high, the aqueous phase viscosity of the product increases, but the hydrophobic silicone oil cannot fully shield, and the product's ion resistance and conditioning properties deviate; when this ratio is too low, the proportion of hydrophobic silicone oil is too high and is located on the periphery of the latex particles, so that when alkali is added for neutralization, the proportion of acid monomers is too small, and the molecular chain cannot be effectively unfolded, resulting in lower viscosity and lower transparency.

[0105] By comparing Example 2-3 with Comparative Examples 3-4 and 5-6, it can be found that the ratio of anions to nonions in the second-step pre-emulsion S2 and the total emulsifier is very critical to the emulsion polymerization process. When the anion ratio is too high, the hydrophobic silicone oil cannot be effectively emulsified, resulting in insufficient polymerization of the product silicone oil, and the product cannot pass the high-temperature accelerated stability test due to the floating oil problem; when the anion ratio is too low, the nonion is affected by the cloud point during the high-temperature polymerization reaction and cannot form particularly stable micelles. The final emulsion is prone to slag during high-temperature storage.

[0106] By comparing Examples 5-6 with Comparative Examples 7-8, it can be found that the selection of silicone oils of different viscosities has a great influence on the product performance. Silicone oils with too high a viscosity cannot be effectively dispersed and emulsified in this system, thereby causing product instability. When the viscosity of the silicone oil is too low, it cannot form an effective shielding effect when polymerized to the main chain, and cannot effectively help the product's ion resistance and conditioning properties.

[0107] By comparing the results of Example 4 with Comparative Example 9, it can be found that the introduction of ester monomers into the second step pre-emulsion S2 not only causes insufficient monomer elimination process and a strong product odor, but also reduces the proportion of external acid and silicone monomers in the molecular chain, making the product's performance in the water phase and in dispensing insufficient. By comparing the results of Example 4 with Comparative Example 10, it can be found that the monomers are directly added without steps, resulting in a strong product odor, and because the monomers are added together, a reasonable distribution of siloxane and hydrophilic acid is not achieved, and its thickening, transparency and ion resistance are not effective.

[0108] By comparing the results of Example 1 with those of Comparative Example 11, it can be found that when the acid monomer ratio is too low, the polymer chain segments cannot be opened after adding alkali, which manifests as emulsion demulsification.

[0109] Through the results of Example 1 and Comparative Example 12, it can be found that the ordinary vinyl-containing polydimethyl silicone oil has a large steric hindrance during the reaction, the polymerization is not sufficient, and there is floating oil after storage, and the emulsion does not have application characteristics; through the comparison of the results of Example 1 and Comparative Example 13, it can be found that when dimethyl silicone oil that does not participate in the reaction is added to the emulsion, the coating effect of the product is not good, and the emulsion does not have application characteristics.

[0110] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A conditioning acrylic suspension thickener, characterized in that: The invention is prepared from raw material components with a mass percentage of 20%-35% and deionized water with a mass percentage of 65%-80%, wherein the raw material components include the following components with a mass percentage: 10.0-75.5% of hydrophilic monomer, 15.0-85.0% of hydrophobic monomer, 0-3.0% of cross-linking monomer, 0.5-25.0% of siloxane containing double bonds, 0.1-5.0% of emulsifier, and 0.1-1.0% of initiator; The double-bond-containing siloxane in the raw material component is selected from at least one of vinyl hydrogen-containing siloxane and divinyl hydrogen-containing siloxane, and the corresponding silicone oil viscosity is 5-20CS; The hydrophilic monomer is selected from at least one of maleic anhydride, itaconic acid, itaconic acid salt, acrylic acid, acrylate, methacrylic acid, methacrylate, citraconic acid, citraconic acid salt, fumaric acid, fumarate, crotonic acid, crotonate, aconitic acid or aconitate; The hydrophobic monomer is selected from at least one of styrene, monobutyl itaconate, vinyl acetate, methyl acrylate, ethyl acrylate, butyl acrylate, isopropyl acrylate, isooctyl acrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isopropyl methacrylate, isooctyl methacrylate or hydroxyethyl methacrylate; The emulsifier is prepared by compounding a nonionic emulsifier and an anionic emulsifier, wherein the anionic emulsifier is selected from at least one of sodium succinic acid sulfonate, sodium diisobutylnaphthalene sulfonate, sodium dodecylbenzene sulfonate or sodium dodecyl sulfate; the nonionic emulsifier is selected from at least one of span-80, tween, alkylphenol polyoxyethylene ether or isomeric alcohol polyoxyethylene ether; The conditioning acrylic acid suspension thickener is prepared by a preparation method comprising the following steps: 1) dissolving 17-90% of the total weight of anionic emulsifier in 150-200 parts by weight of water, then adding hydrophobic monomer, hydrophilic monomer and crosslinking monomer, and stirring in an emulsifying kettle to form a pre-emulsion S1; 2) dissolving a nonionic emulsifier and an anionic emulsifier in 10 to 40 parts by weight of water at a ratio of 1:4 to 1:5, wherein the anionic emulsifier accounts for 5 to 50% of the total weight of the anions, and then adding a siloxane containing a double bond and a hydrophilic monomer acid, wherein the weight ratio of the siloxane containing a double bond to the hydrophilic monomer acid is 1:5 to 1:1, and stirring in an emulsifying kettle to form a pre-emulsion S2; 3) dissolving nonionic and anionic emulsifiers in 130-200 parts by weight of water in a ratio of 1:1 to 1:4, wherein the anionic emulsifier accounts for 5-33% of the total weight of the anionic emulsifier, and adding the mixture to a reaction kettle; dropping the pre-emulsion S1 obtained in step 1) into the reaction kettle, adding 50-90% of the total weight of the initiator to initiate polymerization at a reaction temperature of 80-90° C., and keeping the mixture warm for 1-1.5 hours after the dropping is completed; 4) adding the pre-emulsion S2 obtained in step 2) dropwise into the reaction kettle, adding 10-50% of the total weight of the initiator to initiate polymerization at a reaction temperature of 80-90° C., and keeping the temperature for 0.5-3 hours after the addition is completed; Wherein, the total weight ratio of the nonionic emulsifier to the anionic emulsifier is 1:10 to 1:

4.

2. The conditioning acrylic suspension thickener according to claim 1, characterized in that: The crosslinking monomer is selected from olefins containing two unsaturated double bonds.

3. The conditioning acrylic suspension thickener according to claim 2, characterized in that: The cross-linking monomer is at least one of N,N'-methylenebisacrylamide, ethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, triethylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate or diallyl phthalate.

4. The conditioning acrylic suspension thickener according to claim 2, characterized in that: The initiator is a water-soluble persulfate initiator.

5. The conditioning acrylic suspension thickener according to claim 4, characterized in that: The initiator is at least one of ammonium persulfate, sodium persulfate or potassium persulfate.

6. A composition containing an ion-resistant suspended polymer, characterized in that: Based on the total weight of the composition, the following components are included: (a) 0.01 to 15% of a conditioning acrylic suspension thickener according to any one of claims 1 to 5; (b) 10 to 30% of a detersive surfactant; (c) 0.01 to 5% of a conditioning agent; (d) The balance is aqueous carrier.

7. The composition according to claim 6, characterized in that Based on the total weight of the composition, the following components are included: (a) 0.5-8% of a conditioning acrylic suspension thickener; (b) 15-25% of a detersive surfactant; (c) 0.1-2% conditioning agent; (d) The balance is aqueous carrier.

8. The composition according to claim 6 or 7, characterized in that The component (b) heavy detersive surfactant is selected from at least one of sodium laureth sulfate, alkyl amino oxides, alkyl betaines, cocamidopropyl betaine, disodium cocoamphodiacetate, alkyl sulfobetaines, alkyl glycinates, alkyl carboxyglycinates, alkylaminopropyl hydroxy, acyl taurates and acyl glutamates, sodium lauryl sulfate, sodium lauryl polyether sulfate, C12-16 alkyl glucoside or sodium lauroyl glutamate.

9. The composition according to claim 8, characterized in that The alkyl and acyl groups have 8 to 19 carbon atoms.

10. The composition according to claim 6 or 7, characterized in that The conditioning agent in the component (c) is selected from at least any one of polyquaternium salts, quaternized proteins, cationic guar gums or water-soluble silicone oils.

11. The composition according to claim 10, characterized in that The conditioning agent is selected from at least any one of guar hydroxypropyltrimonium chloride, polyquaternium-10 or polydimethylsiloxane.

12. The composition according to claim 6 or 7, characterized in that The aqueous carrier in the component (d) is selected from water and one or a mixture of sodium chloride, pH regulator, antidandruff agent, flavor, emulsifier, chelating agent, sunscreen, preservative, pearlescent agent.

13. The composition according to claim 12, characterized in that The aqueous carrier comprises the following components in percentage by weight, based on the total weight of the aqueous carrier: 0-1% pH adjuster; 0-3% anti-dandruff agent; 0-3% flavor; 0-3% emulsifier; 0-0.5% chelating agent; 0-1% sunscreen; 0-1% preservatives; 0-1% pearlescent agent; 0-1% petal or particle suspension; The rest is water.

14. The composition according to claim 12, characterized in that The anti-dandruff agent is selected from at least one of climbazole, pyrithione zinc, piroctone olamine salt or triclosan; The preservative is selected from at least one of kasone, paraben, sodium benzoate, salicylic acid, DMDM ​​hydantoin or phenoxyethanol; The fragrance is selected from artificial synthesis or natural essence.

15. The method for preparing the composition according to any one of claims 6 to 14, characterized in that: The method comprises the steps of stirring and mixing the components (a) to (d) according to a proportion until they are in a uniform state.

16. Use of the composition according to any one of claims 6 to 14 or the composition prepared by the preparation method according to claim 15 as a shampoo.

Citation Information

Patent Citations

  • Water-repellent modified association thickening agent and preparation method thereof

    CN102675951B

  • An antifreeze acrylate suspension thickening emulsion and its preparation method

    CN103772625B

  • Thickener for emulsion paint and preparation method thereof

    CN109777174A

  • Freezing-resistant acrylate suspended thickening emulsion and preparation method thereof

    CN103772625A

  • Hydrophobic modified associative thickener and preparation method thereof

    CN103788283A